RESEARCH ON SELECTION OF COMPOSITION AND TECHNOLOGY OF GEL PRODUCTION FROM OLEUM HIPPOPHAES (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
The development of the technology of laboratory samples of gels was carried out on the basis of the center of practical skills in the specialty "Pharmacy" of the Institute of Pharmaceutical Education and Research.